The author of 1 John uses the multiple references to his ‘writing’ as a mechanism to establish different affects and effects - Merwe, Dirk G. van der (HTS Teologiese Studies / Theological Studies, 2018)
In 1 John, the author refers several times explicitly to himself (also once in the plural, 1:4) for writing (γράφειν) certain things with the following purposes in mind, (that, ἵνα): ‘our joy may be complete’ (1:4); ‘you may not sin’ (2:1); and ‘you may know that you have eternal life’ (5:13). In 2:26, he implicitly states that he has also written ‘these things’ (ταῦτα) that (ἵνα) they might be victorious over the deceivers. This is the only book in the New Testament where such a high frequency of an author’s reference to his own writing occurs. In 1 John it is used as part of a fixed phrase (ταῦτα γράφω/ἔγραψα ὑµῖν ἵνα) in the author’s rhetoric. This essay focusses on the primary and secondary objectives for writing 1 John per se, and on conceivable lived experiences fostered by the fixed phrase ‘ταῦτα γράφω ὑµῖν ἵνα’ [I am writing these things to you so that …], as well as the mechanisms the author used to unleash these lived experiences linked with these fixed phrases. The following aspects determine the structure of this essay: the author’s objectives, the expectancy of his writing, the credibility of his writing and the mechanisms the author used through which lived experiences could have been fostered to influence and convince his readers that Jesus is the Son of God.
free
Keywords: Bible. Epistle of John I – Authorship; Bible. Epistle of John I – Criticism; Literary; Bible. Epistle of John I – Theology; Experience (Religion); Open access; Peer reviewed; Rhetoric in the Bible